Monoclonal Gammopathy of Undetermined Significance After Kidney Transplantation: Single-Center Experience. Issue 11 (November 2017) - Alfano, Gaetano; Fontana, Francesco; Colaci, Elisabetta; Messerotti, Andrea; Bettelli, Francesca; Potenza, Leonardo; Luppi, Mario; Cappelli, Gianni
Abstract : Background: Monoclonal gammopathy of undetermined significance (MGUS) is an asymptomatic premalignant plasma cell disorder. Prevalence and clinical outcomes of MGUS in kidney transplant (KT) recipients have been previously reported in few studies with conflicting results. Methods: We conducted a retrospective study in a population of 548 KT recipients transplanted between 1998 and 2015. Results: Thirty-nine (8.1%) subjects developed MGUS after KT. At diagnosis of MGUS, the average age was 52 ± 9.2 years, and 23% of the patients were younger than 50 years. Occurrence of MGUS was not influenced by age and sex. After a mean follow-up of 7.8 years, only 1 (2.5%) patient progressed to multiple myeloma. We found no differences in the incidence of solid and hematological malignancies, serious infections, graft failure, and mortality between KT patients with MGUS and a matched cohort of KT recipients without MGUS. The MGUS group had a significantly higher prevalence of monoclonal B cell lymphocytosis, premalignant condition poorly described in KT recipients. Prior history of glomerulonephritis or interstitial nephritis, as cause of renal failure, represented the only predictive factor for MGUS development. Conclusions: MGUS is a premalignant disorder frequently encountered in KT recipients. We found no differences in clinical outcomes between MGUS patients and KT controls. Abstract : This large retrospective analysis reports an update on the incidence of posttransplant monoclonal gammopathy of uncertain significance of 8 percent without clear predisposing factors or infection with EBV, CMV, BK or JC. Supplemental digital content is available in the text.